Stardom and Spending: Correlating the Influence of Celebrity-Based Product Placements in ABS-CBN Films on Fan-Consumer Purchasing Intentions and Behaviors - Acosta, Arabella R.; Del Rosario, Aliyah Monina J.; Guevara, Sofia Kristen D.; Salazar, Jeremy Kirsten R.; Arcinas, Myla M. (Future Science / FSH-PH Publications, 2025)
This study examines the influence of celebrity-based product place-ments featuring Vice Ganda in ABS-CBN films on fan-consumers' per-ceptions, purchasing intentions, and purchasing behaviors. Using a quantitative correlational research design with 163 fan-consumers from Metro Manila, the study employed survey instruments adapted from Kumar's (2011) questionnaire and grounded in Ohanian's (1990) Source Credibility Tri-Model. Results revealed that fan-consumers held positive perceptions of Vice Ganda's product placements (Mdn = 4.00), exhibited high purchasing intentions (Mdn = 4.00), and demonstrated strong purchasing behaviors (Mdn = 4.00). Correlation analysis re-vealed a strong positive relationship between purchase intentions and purchasing behaviors (r = 0.74, p < .01), a weak positive relationship between perceptions and purchase intentions (r = 0.19, p < .05), and a negligible relationship between perceptions and purchasing behaviors (r = 0.09, p = .25). These findings support a sequential influence model, suggesting that celebrity endorsements operate through a perception-intention-behavior pathway rather than directly from perception to behavior. The study contributes to the theoretical understanding of celebrity influence mechanisms and practical applications for market-ers seeking to optimize product placement strategies in entertainment media.